Optimalisasi Peran Sekolah dalam Edukasi Pencegahan Adiksi dan Kesehatan Reproduksi pada Siswa - Masiah Masiah; Laras Firdaus; Siti Nurhidayati; Siti Rabiatul Adawiyah; Lalu Jaswandi; Nofisulastri Nofisulastri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Adolescents need structured health education because they are in a developmental phase that is vulnerable to risky behaviors, including addiction and limited understanding of reproductive health. Schools have a strategic role as preventive educational spaces that are closely connected to students' daily lives. This community service activity aimed to optimize the role of schools in educating students about addiction prevention and reproductive health at MTs Al-Hamidiyah NW Sidemen. The activity used a school-based health education method with a participatory approach through seminars, interactive lectures, discussions, question-and-answer sessions, presentation media, and reproductive health posters. Program success was evaluated through student participation observation, records of responses during question-and-answer sessions, activity documentation, and implementation indicators. The results showed that schools can serve as effective facilitators of adolescent health education. Students showed attention, engagement, and positive responses during the activity. Visual media helped clarify sensitive topics and made them easier to understand. This activity confirms that integrated education on addiction prevention and reproductive health should be continued through school guidance programs, counseling services, and collaboration with parents.